Distinct gestational trophoblastic neoplasia - different entities, specific management - Brandão, Pedro; Silva-Rocha, Juliana; Pinto, Ana Rita; Costa, Fernanda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Gestational trophoblastic diseases are abnormalities of the trophoblastic tissue development. They have Β-hCG as tumour marker, similar clinical manifestations but different pathological features, management and prognosis. Gestational trophoblastic neoplasia includes all forms of gestational trophoblastic disease that are invasive and/or metastasize and correspond to 10% of this group of diseases. The authors performed a retrospective review of all patients referred to our department between 1st January 2011 and 30th June 2016. Presenting symptoms, Β-hCG levels, obstetric and personal history and microscopic features were reviewed. 4 cases were identified - 2 invasive complete and 1 partial hydatidiform moles and 1 placental site trophoblastic tumour. Management and follow-up were individualized. Neither persistence nor recurrences were diagnosed after primary treatment. These case series highlights the importance of an accurate diagnosis and a long-term follow-up considering the risk of persistency or malignancy, as gestational trophoblastic neoplasia usually have good response to the adequate therapy.